An initial learning experience of tracheal intubation with video laryngoscope: Experiences from a novice PGY. Issue 19 (14th May 2021) - Shih, Chai-Bae; Wu, Yu-Hwa; Lin, Chung-Ren; Tseng, Chia-Chih Alex
Abstract : Abstract: Tracheal intubation is an essential technique for many healthcare professionals and one of the mega code simulations in advanced cardiac life support. In recent years, video laryngoscopy (VL) has provided a rescue for difficult airways during intubation and has proven to have higher success rates. Moreover, VL facilitates a more rapid learning curve for inexperienced doctors. In this article, we report 16 cases intubated with VL by a novice doctor of postgraduate year 1, who shared the learning experience and the difficulties encountered in this case series. We also conducted a statistical analysis to evaluate the learning outcomes of the trainee after 1 month. Our results showed that the overall first-shot success rate was 81.3% for the 16 objectives. Over time, improvements in intubation performance measures, including shortened duration and lower Intubation Difficulty Scale score, have been observed. In this learning project, we found that limitation of mouth opening (<2.5 fingers wide) is an important risk factor for predicting the initial difficulty of tracheal intubation on the novice trainee. For inexperienced doctors, VL produces high first-shot success rates for tracheal intubation and may be useful for training their performance in a short period of time. In addition, mouth opening <3 fingers wide may result in difficult intubation by novice doctors.